2021
DOI: 10.1002/agj2.20708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cover crops forage nutritive value in Oklahoma winter wheat systems

Abstract: Winter wheat (Triticum aestivum L.) is a valuable crop in the southern Great Plains that grows from fall to spring, with fields then typically fallowed through the summer. Adding grazeable cover crops to the fallow period could increase farm profitability.The objective of this study was to determine eight different cover crops' nutritive value and simulated stocker calf performance. Cover crops were established in late spring 2016 and 2017 in Chickasha and Perkins, OK. At 6 wk after planting, two simulated gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Differing from the findings of Blanco-Canqui et al (2012), Boyer et al (2018) observed in a 29-year cotton and winter cover crop experiment in Tennessee cotton production that the highest net present value yields occurred when CC were not used. In grazing operations specifically, Horn et al (2021) suggested that short cycle drought resistant legume CC in Oklahoma could result in stocker cattle grazing profitability when managed appropriately. While total yield was negatively affected by the addition of legume-based crops, the nutrient value of forage was enhanced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing from the findings of Blanco-Canqui et al (2012), Boyer et al (2018) observed in a 29-year cotton and winter cover crop experiment in Tennessee cotton production that the highest net present value yields occurred when CC were not used. In grazing operations specifically, Horn et al (2021) suggested that short cycle drought resistant legume CC in Oklahoma could result in stocker cattle grazing profitability when managed appropriately. While total yield was negatively affected by the addition of legume-based crops, the nutrient value of forage was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…In grazing operations specifically, Horn et al. (2021) suggested that short cycle drought resistant legume CC in Oklahoma could result in stocker cattle grazing profitability when managed appropriately. While total yield was negatively affected by the addition of legume‐based crops, the nutrient value of forage was enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, relative forage quality (RFQ) of samples was calculated by the formula: RFQ = DMI × TDN/1.23 (Undersander & Moore, 2002). Total digestible nutrients (TDNs) were determined from ADF values using the formula: TDN legume = 88.875 – (0.812 × %ADF) (Horn et al, 2021).…”
Section: Methodsmentioning
confidence: 99%